Análise e tolerância de risco nas atividades de manutenção de elevadores de passageiros e cargas periculosidade por energia elétrica - Grando, Luciano Roberto (Universidade do Vale do Rio dos Sinos, 2016)
This technical paper presents an analysis of requirements and procedures to reduce the risk of electric energy in the maintenance activities of elevators, identifying the risks and hazards involved in the tasks, and the necessary control measures for the elimination, neutralization or mitigation of the effects Of the risk by electric energy to the workers, aiming at thus to characterize the dangerousness foreseen in Annex IV of NR-16.
Keywords: Elevadores; Manutenção; Análise de risco; Energia elétrica; Periculosidade; Anexo IV NR-16